Identification Of Putative Virulence Factors Of Leptospira Interrogans Using A Yeast Model - Lai, Weng Yu (2019)
Internalization and intracellular proliferation of pathogenic bacteria Leptospira interrogans (L. interrogans) in their host is induced by pathogenic proteins known as virulence factors (VFs) which target molecular mechanisms, cellular processes and eukaryotic structures that are conserved among eukaryotes. Yeast, Saccharomyces cerevisiae (S. cerevisiae), is a popular eukaryotic model that is used to identify bacterial VFs. The goal of this study was to identify L. interrogans putative virulence factors by expressing them in yeast and examining the putative VFs impact on yeast growth. A total of 288 L. interrogans putative virulence genes were selected through a bioinformatic approach and literature review. Of the 288 selected putative virulence genes, 226 putative virulence genes were successfully cloned in the yeast expression plasmid and expressed in yeast using a 96-well plate format. The cell viability of yeast expressing putative virulence factors was verified using a liquid medium method and yeast serial dilution spotting assay. Eleven L. interrogans putative VFs were found inhibiting yeast growth and they were investigated for their localization in yeast and VF-yeast protein interaction. A green fluorescent protein (GFP) was fused to the C-terminal of the VFs to investigate the localization of putative VFs in yeast with the use of a fluorescent microscope. In conclusion, the yeast model is a simple and effective model to identify bacterial VFs that target conserved molecular mechanisms and cellular processes among yeast and human cells. This study has provided some preliminary information for the future study on L. interrogans invasion and evasion mechanisms.